Analisa Decision Tree Dalam Pengolahan Data Siswa - Sianturi, Fricles Ariwisanto (LPPM UNIKA Santo Thomas Medan, 2018)
Graduation rate is one of the main problems in a college foundation. The higher graduation of students in an educational institution will further increase the popularity of the foundation. Likewise, if there is a decrease in graduation rates, then the foundation or school experiences a decline in popularity, thus allowing the decline of interested persons / candidates to enter the foundation in the following years. The purpose of the study is to find out which factors are the most dominant which influence the graduation rate of a student, so that in the future it is expected that the school will be able to see the final results of student graduation in the following years. The output of this research is to find out which factors are the most dominant which influence the graduation rate of a student, so that in the future, it is expected that the school will be able to see the results of student graduation in the following years.